Penggunaan Zinc Oxide Eugenol Sebagai Sealer Pada Perawatan Saluran Akar Gigi 11: Laporan Kasus - Muhammad Arib Rafi; Nurdin, Denny (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Irreversible pulpitis is a condition that indicates that the inflamed pulp cannot heal, so it requires treatment in the form of root canal treatment. The success of root canal treatment depends on the process of cleaning, shaping and sealing the root canal. To obtain a good seal, obturation materials such as gutta-percha and sealer are used. The function of the sealer is to fill the space between the gutta-percha and the root canal wall. Zinc oxide eugenol is one of the most commonly used sealer materials because it has antimicrobial effects, is radiopaque, easy to obtain and apply, and is economical. This case report reports a 24 year old female patient who came with complaints of cavities in her front teeth since 1 year ago. Based on the examination results, the patient's diagnosis was irreversible asymptomatic pulpitis with normal apical tissue of tooth 11. The treatment carried out was root canal treatment on tooth 11. The results of the treatment showed that zinc oxide eugenol could be a good sealer and did not cause abnormalities in the periapical tissue.